PC Splice-Site Variant c.1825+5G>A Caused Intron Retention in a Patient With Pyruvate Carboxylase Deficiency: A Case Report - Tao, DongYing; Zhang, HuiQin; Yang, Jingmin; Niu, HuanHong; Zhang, JingJing; Zeng, Minghua; Cheng, ShengQuan (Frontiers in Pediatrics, 2022)
Background Pyruvate carboxylase deficiency (PCD; MIM#266150) is a rare autosomal recessive disorder characterized by a wide range of clinical features, including delayed neurodevelopment, elevated pyruvate levels, lactic acidosis, elevated ketone levels, and hyperammonemia. The pyruvate carboxylase (PC) gene was identified to be the disease-causing gene for PCD. A novel homozygous splice variant in the PC gene was identified in a Chinese boy, but the pathogenicity is still unclear. The objective of the present study was to determine the effect of this splice-site variant by reverse transcription analysis. Methods We reported the clinical course of a 20-month-old Chinese pediatric patient who was diagnosed with PCD using whole-exome sequencing (WES). The effects of the variant on mRNA splicing were analyzed through the transcript analysis in vivo. Results The results of metabolic blood and urine screening suggested PCD by employing tandem mass spectrometry. WES revealed a novel homozygous splice-site variant (c.1825+5G>A) in the PC gene. in vivo transcript analysis indicated that the splice-site variant caused the retention of 192 bp of the intron. Conclusion Thus, c.1825+5G>A was established as a pathogenic variant, thereby enriching the mutational spectrum of the PC gene and providing a basis for the genetic diagnosis of PCD.